NF-kappaB Is Involved in the Regulation of EMT Genes in Breast Cancer Cells - Pires, Bruno R. B.; Mencalha, Andre L.; Ferreira, Gerson M.; de Souza, Waldemir F.; Morgado-Díaz, José A.; Maia, Amanda M.; Corrêa, Stephany; Abdelhay, Eliana S. F. W. (PLOS ONE, 2017)
The metastatic process in breast cancer is related to the expression of the epithelial-to-mesenchymal transition transcription factors (EMT-TFs) SNAIL, SLUG, SIP1 and TWIST1. EMT-TFs and nuclear factor-κB (NF-κB) activation have been associated with aggressiveness and metastatic potential in carcinomas. Here, we sought to examine the role of NF-κB in the aggressive properties and regulation of EMT-TFs in human breast cancer cells. Blocking NF-κB/p65 activity by reducing its transcript and protein levels (through siRNA-strategy and dehydroxymethylepoxyquinomicin [DHMEQ] treatment) in the aggressive MDA-MB-231 and HCC-1954 cell lines resulted in decreased invasiveness and migration, a downregulation of SLUG, SIP1, TWIST1, MMP11 and N-cadherin transcripts and an upregulation of E-cadherin transcripts. No significant changes were observed in the less aggressive cell line MCF-7. Bioinformatics tools identified several NF-κB binding sites along the promoters of SNAIL, SLUG, SIP1 and TWIST1 genes. Through chromatin immunoprecipitation and luciferase reporter assays, the NF-κB/p65 binding on TWIST1, SLUG and SIP1 promoter regions was confirmed. Thus, we suggest that NF-κB directly regulates the transcription of EMT-TF genes in breast cancer. Our findings may contribute to a greater understanding of the metastatic process of this neoplasia and highlight NF-κB as a potential target for breast cancer treatment.